Applications and techniques in information security : 8th International Conference, ATIS 2017, Auckland, New Zealand, July 6-7, 2017, Proceedings /: 8th International Conference, ATIS 2017, Auckland, New Zealand, July 6-7, 2017, Proceedings. (2017) - Unknown
No abstract available